Quantitative assessment of pacific salmon Oncorhynchus by acoustic method in the Amur River basin - E. V. Podorozhnyuk; A. I. Degtev (Известия ТИНРО, 2025)
Assessment of the pacific salmon run to the Amgun River in 2022–2024 by acoustic method is presented. The NetCor-3 software and hardware complex was used. A technique for sonar registration of fish was developed and tested in conditions of the Amur River basin. Optimal technical parameters of the equipment for the fish counting at the registration site were determined